HEPATOPROTECTIVE ACTIVITY OF CTIVITY OF CTIVITY OF ENICOSTEMMA AXILLARE IN CARBON TETRACHLORIDE INDUCED HEPATOTOXICITY IN ALBINO RATS - V. N. GITE; S. B. TAKTE; R. D. POKHARKAR (The Bioscan, 2010)
The present study was conducted to evaluate the hepato-protective activity of pet ether, chloroform, methanol and water extract of aerial parts of Enicostemma axillare are evaluated in CCl4 -induced hepatotoxicity in albino rats. Silymarin (200mg/kg) was given as reference standard. The methanolic and water extracts of aerial parts of Enicostemma axillare have shown very significant hepatoprotection against CCl4 -induced hepatotoxicity in albino rats in reducing serum total bilirubin, direct bilirubin, SGPT and SGOT levels.